2013
DOI: 10.1210/en.2012-2077
|View full text |Cite
|
Sign up to set email alerts
|

5α-Reductase Inhibition Suppresses Testosterone-Induced Initial Regrowth of Regressed Xenograft Prostate Tumors in Animal Models

Abstract: Androgen deprivation therapy (ADT) is the standard treatment for patients with prostate-specific antigen progression after treatment for localized prostate cancer. An alternative to continuous ADT is intermittent ADT (IADT), which allows recovery of testosterone during off-cycles to stimulate regrowth and differentiation of the regressed prostate tumor. IADT offers patients a reduction in side effects associated with ADT, improved quality of life, and reduced cost with no difference in overall survival. Our pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…In our study, DHT decreased when progesterone was present but DHT increased in the absence of precursor progesterone. When LuCaP xenografts were treated with dutasteride there was an increase in testosterone while our in vitro study with 22RV1 cells a decrease was observed [40,41]. These differences can be attributed to the inherent differences between each cell line and how they uniquely adapt to treatment as well as how the tumor microenvironment in the in vivo models influences steroidogenesis.…”
Section: Discussionmentioning
confidence: 66%
“…In our study, DHT decreased when progesterone was present but DHT increased in the absence of precursor progesterone. When LuCaP xenografts were treated with dutasteride there was an increase in testosterone while our in vitro study with 22RV1 cells a decrease was observed [40,41]. These differences can be attributed to the inherent differences between each cell line and how they uniquely adapt to treatment as well as how the tumor microenvironment in the in vivo models influences steroidogenesis.…”
Section: Discussionmentioning
confidence: 66%
“…Tumor tissue samples were fixed immediately after dissection in 10% formalin overnight, dehydrated in ethanol, cleared in xylene, and embedded in paraffin blocks, as previously described (26). Six micrometer-thick sections were prepared, mounted on positive charged slides (Fisher Biotech, Pittsburgh, PA), and air-dried overnight.…”
Section: Methodsmentioning
confidence: 99%
“…We observed that finasteride or dutasteride caused an initial inhibition of regrowth and then the tumors resume growth at the same rate as that of the control group as measured by tumor volume ( Figure 2 ). The initial regrowth inhibition by 5 alpha-reductase inhibitor was confirmed by reduced Ki-67 staining and BrdU incorporation assay 53. Both assays showed a statistically significant inhibition (~10-fold) of proliferation index by 5 alpha-reductase inhibitors during the initial phase of regrowth, but not after prolonged exposure to testosterone.…”
Section: Introductionmentioning
confidence: 76%